CORRELATION OF AXILLARY TEMPERATURE WITH RECTAL TEMPERATURE IN CLINICALLY UNSTABLE NEONATES - Ahmad, Irshad; Khan, Qamar Ali; Iqbal, Hamid; Khattak, Khushal Khan; Rehman, Habibur (Journal of Postgraduate Medical Institute, 2012)
Objectives: To test the hypothesis that axillary temperature may not correlate well with rectal temperature in unstable neonates and to compare the predictive value of axillary temperature recording in unstable neonates with that of healthy neonates. Methodology: This cross-sectional and analytical study. Neonates from birth till the age of one month were included in the study. Axillary temperature and rectal temperature were recorded upon arrival to the unit, using digital thermometers. Results: At arrival, 109 neonates were categorized as stable and 117 as unstable. There were no statistically significant differences in their demographic data such as gender, gestational age, postnatal age and weight of the neonates in the two groups. Over all mean axillary temperature was 97.020F (SD±2.5) and mean rectal temperature was 97.990F (SD±2.21). The overall correlation between the axillary and rectal temperature was 0.632 (p<0.001). A significant difference (P-value <0.001) in the Pearson correlation (r) between axillary and rectal temperature recording in the two groups was found. A significant difference was also observed in regression lines between the two groups. Conclusions: Axillary temperature measurement is not a reliable method of documenting the arrival temperature in clinically unstable neonates.